Determination of alkaloids in samples submitted to the Center for Research and Advanced Studies in Animal Health (CIESA) compatible with strychnine poisoning during the period 2018-2021 - Valladares-Carranza, Benjamin (2025)
The objective of this study was to analyze cases of dogs diagnosed with strychnine poisoning at the Center for Research and Advanced Studies in Animal Health (CIESA), Mexico. This is a retrospective study based on information from cases that occurred between 2018 and 2021, in which clinical records from the toxicology department were analyzed and systematized. It should be noted that strychnine was identified in the laboratory using a qualitative test. A descriptive method was applied for reporting results, considering variables of epizootiological interest (geographical area of occurrence, type of sample, age, and breed of the affected animals). A total of 17 cases were received from the State of Mexico: Almoloya de Juárez (n = 3), Ixtlahuaca (n = 2), San Mateo Atenco (n = 1), Temoaya (n = 3), Toluca (n = 5), and Valle de Bravo (n = 1), and from the State of Querétaro (n = 2). In 2018, 6 cases were recorded; in 2019, 2020, and 2021, there were 4, 4, and 3 cases, respectively. Of the 17 cases, a total of 25 samples were processed in the Toxicology Laboratory and 3 in the Necropsy Unit, where samples were collected from three dogs. The anatomopathological study consistently revealed generalized congestion of the conjunctivae, liver, kidney, gastric mucosa, and brain. The overall positivity rate for strychnine was 68%. Liver samples tested positive in 75% of cases, gastric content in 57.1%, and prepared bait in 66.6%. The most exposed breed was hybrid animals, ranging from 2 to 6 years of age. It is concluded that the regulation, monitoring, and registration of all substances sold in our country is imperative to prevent and control any acts that may endanger animal life.